PENGEMBANGAN BAHAN AJAR BAHASA ARAB BERBASIS TEORI BELAJAR KONSTRUKTIVISME UNTUK MAHASISWA - Hamid, M. Abdul; Hilmi, Danial; Mustofa, M. Syaiful (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2019)
Teaching materials are very important in the process of learning Arabic; therefore, the teaching and learning process requires motivation to increase student language competence. With regard to the material taught in higher education, the urgency of constructivism theory has not yet fulfilled in the success of learning. As a result, the theory becomes a necessity for the development of teaching material to strengthen their interest in developing language competencies. This study intended to develop Arabic teaching materials for students in Islamic Religious Colleges so that they do not depend on books sourced from Arab countries that have different cultures than local cultures. Based on the results of the needs analysis, the textbook product was produced, which is named al-Arabia li al-Hayah along with inputs from experts. The results of this book trial showed that this book was effective to meet the needs of students in improving Arabic competence through mastery of vocabulary in their environment.